Development of process layout and multiple robot simulation : a case study - Wickramasinghe, Nuwan Ujith; Lin, Than; Manukid Parnichkun; Bohez, Erik L.J. (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
With the development of the technology, clients expectations vary. Most commonly they expect good quality products for a cheaper price and within a less amount of time. To fulfill the expectations of the customer the manufactures are concentrating to improve their manufacturing process by automating the manufacturing process. During this automation process the most of the workers are replaced by robots. In an automated manufacturing line there are several work cells, some may include individual robots and some work cells have multiple robots depending on the requirement of the process. When there are multiple robots in a single work cell the cycle time will be reduced. But when there are multiple robots in a single work cell, the collision between the components and the waiting time of the robot are some of main issues which needed to be considered. By using robot synchronization the collision can be avoided and the waiting time can be reduced. Also most importantly the manufactures can achieve optimum productivity. Today there are many ways to apply synchronization to the robots. One way of doing it by developing the virtual cad design of the actual cell and verifying it. Then the synchronization is carried out. There are many softwares which could be used to carry out this process. But for this study I have used the Tecnomatix PLM software. This software is highly used in the industry today. To develop the synchronization, firstly the existing arc welding work cell was developed by adding two robots instead of one robot. Then the cell is rearranged to find the optimum placement of the robots. Next a weld path was developed and the robot is taught to move in the path. Finally the synchronization will be carried out. In order to synchronize, both robots and PLC signal will be generated and then logic will be generated in the Module. This module feature is considered as the PLC of the simulation. The logic defined in the Module can be used to develop actual PLC program in the future. In the existing work cell the arc welding tool path is carried out using an approximation method. As final outcome of my study Ill be suggesting a much more accurate method to generate the arc welding tool path. And will also be providing the knowledge about the synchronization process.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering in Mechatroinc Engineering, School of Engineering and Technology
Capstone Project (B. Sc.) - Asian Institute of Technology, 2015
Keywords: Robot vision -- Data processing